SISTEM INFORMASI “BOOK SUMMARY” PADA JENJANG SMP BERBASIS WEBSITE MENGGUNAKAN METODE PERSONAL EXTREME PROGRAMING (STUDI KASUS SMPN 4 TALIWANG) - Anggraini, Mustika; Albar, Moh. Ali; Zubaidi, Ariyan (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2025)
The availability of printed textbooks as the main learning resource remains a challenge in several schools, including SMP Negeri (SMPN) 4 Taliwang located in Sumbawa Barat Regency, West Nusa Tenggara. The limited availability of printed textbooks prevents students from fully accessing learning materials. Additionally, the results of the questionnaire indicate that most students prefer shorter texts, which suggests a low level of reading interest among the students. This becomes one of the obstacles in the implementation of learning, especially when the lesson material is presented in the form of long texts. Seeing the existing problem, the author developed a website-based books summary information system using the Personal Extreme Programming (PXP) method. The PXP method was chosen because of its quick cycle time and flexibility in accommodating new user needs, while still focusing on planning and software quality. This system is designed to enhance students' access to school lesson materials in a more concise manner, making them easier to understand, and accessible anytime and anywhere. The test results show that this system is capable of improving students' access to learning materials with a MOS percentage of 86% (excellence category), indicating that the system is functioning well and is suitable for use.